CONSUMER ACCEPTANCE TOWARDS ONLINE GROCERY SHOPPING IN MALANG, EAST JAVA, INDONESIA - Wisynu Ari Gutama; Anggya Puspita Dewi Intani (Agricultural Socio-Economics Journal, 2017)
Online grocery shopping in Indonesia has been applied by one platform called Happyfresh, which cooperates through many modern supermarkets. One supermarket that conducts this cooperation to supply grocery products is Loka Mart. Currently, online grocery shopping facility that implemented by Loka Mart is still limited and only coverage Jakarta area. Thus, it is necessary to conduct study related to the public acceptance to the online grocery shopping in Malang City as the potential online market due to the level of education of the society. The data are obtained through the questionnaire of 140 respondents of Loka Mart consumer. Technology Acceptance Model (TAM) is employed as the foundation in this study. Besides, visibility, risk perception, and social influence variable – which used in the study of Sherah and Ai-Wen (2003) – analyzing Australian people acceptance towards online grocery shopping – used in this study. Multiple regression analysis, pearson correlation, and biserial point used as analysis instrument in this study. The study result showed that basic model of TAM – which consists of perceived of usefulness, perceived ease of use, and social influence variable – could explain public acceptance in Malang City to the online grocery shopping. Moreover, the visibility and risk perception variable have no effect in explaining public acceptance to use online grocery shopping. This result also shows that, Online Grocery Acceptance Model explains how the behavior and characteristics of the consumers in utilizing online grocery service. Perceived of usefulness is the main factor affecting online grocery acceptant and the perceive ease of use is correlated highly with perceived of usefulness.